2014
DOI: 10.1107/s1600536814006059
|View full text |Cite
|
Sign up to set email alerts
|

Enrofloxacin hydrochloride dihydrate

Abstract: The asymmetric unit of the title compound, C19H23FN3O3 +·Cl−·2H2O [systematic name: 4-(3-carb­oxy-1-cyclo­propyl-6-fluoro-4-oxo-1,4-di­hydro­quin­o­lin-7-yl)-1-ethyl­piperazin-1-ium chloride dihydrate], consists of two independent monocations of the protonated enrofloxacin, two chloride anions and four water mol­ecules. In the cations, the piperazinium rings adopt chair conformations and the dihedral angles between the cyclo­propyl ring and the 10-membered quinoline ring system are 56.55 (2) and 51.11 (2)°. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Polymorphic forms are determined with identical chemical manipulation of enrofloxacin. As previously reported (Miranda‐Calderon et al ., ), structure of enro C elicited by X‐ray diffraction analysis corresponds to solvate form of enrofloxacin hydrochloride with two water molecules (see Fig. ).…”
Section: Resultsmentioning
confidence: 98%
“…Polymorphic forms are determined with identical chemical manipulation of enrofloxacin. As previously reported (Miranda‐Calderon et al ., ), structure of enro C elicited by X‐ray diffraction analysis corresponds to solvate form of enrofloxacin hydrochloride with two water molecules (see Fig. ).…”
Section: Resultsmentioning
confidence: 98%
“…Failure to attain these ratios has been linked to an increase in bacterial resistance and lack of clinical efficacy (20). Synthesis of a solvate of enrofloxacin (enrofloxacin hydrochloride-dihydrate; enro-C) (13) with improved pharmacokinetics has been advanced as means to obtain improved PK/PD ratios (14,15) and, ideally, to achieve theoretical mutant-preventive concentrations (C MAX ≥ 16 MIC) (21). Enro-C exhibits different physicochemical properties from the parent compound, mainly water solubility (13) and pharmacokinetics, as has been so far shown in broilers (15).…”
Section: Discussionmentioning
confidence: 99%
“…A new solvate of enrofloxacin is already available for research (enrofloxacin hydrochloridedihydrate, enro-C) (14), and it has shown improved PK values in broilers (15). Hence, the aim of this trial was to determine the PK and the PK/PD ratios of enrofloxacin from enro R and from enro-C in Syrian golden hamsters while assessing as pharmacodynamic markers the MIC values for methicillin-resistant Staphylococcus aureus, Leptospira interrogans, and Escherichia coli.…”
Section: Introduction Enrofloxacinmentioning
confidence: 99%
“…However, to the best of our knowledge, no commercial preparations Serum and milk concentrations of enrofloxacin in cows intramammarily treated with a new enrofloxacin-polymorph 1) for this route exist in most countries, and the available products for parenteral administration have a pH at or above 10.4; a fact that makes intramammary administration of the drug rather unadvisable (28). However, a new recrystallized enrofloxacin polymorphic form, enrofloxacin hydrochloride-dihydrate (enro-C) (19), has shown higher water solubility than the parent compound and a superior bioavailability than reference enrofloxacin in broiler chicken (12). As a 1.5% suspension, enro-C exhibits a pH of 5.5, and it does not irritate the mammary gland when intramammarily administered (17).…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…The physicochemical characteristics of enro-C include higher water solubility than that of the parent molecule (19). Yet, this feature was not sufficient to make it possible to prepare a solution rather than a suspension of 300 mg of enro-C in 20 mL.…”
Section: Tab 4 Serum Pharmacokinetic Parameters For Enrofloxacin Anmentioning
confidence: 99%